The rare report of unicentric Castleman disease with concurrent myasthenia gravis and paraneoplastic pemphigus: a case report with a focused review of the literature - Cheng, Zeyu; Liu, Wenliang; Hu, Yan (Frontiers in Oncology, 2026)
RationaleCastleman disease (CD) is a rare lymphoproliferative disorder that can be associated with autoimmune manifestations. While paraneoplastic pemphigus (PNP) and myasthenia gravis (MG) have each been reported with CD, their simultaneous occurrence is extremely uncommon. Here, we describe a case of mixed-type unicentric Castleman disease (UCD) complicated by both MG and PNP.Patient concernsA 49-year-old man presented with fluctuating right eyelid ptosis, consistent with ocular MG. Several months later, he developed progressive oral erosions.DiagnosesThe patient was diagnosed with ocular myasthenia gravis (MG) based on fluctuating ptosis and a positive neostigmine test. Chest imaging revealed an anterior mediastinal mass initially suspected to be thymoma. Biopsy and immunopathology of the lips and oral mucosa confirmed PNP, with direct immunofluorescence showing intercellular IgG deposition and serological positivity for envoplakin and periplakin antibodies. After stabilization of systemic symptoms, the mediastinal mass was surgically removed, and histopathological examination confirmed mixed-type UCD. To date, only four previous cases of this triad have been reported in the literature, and the present case represents a mixed-type UCD subtype.InterventionsThe patient was treated with pyridostigmine for MG, systemic corticosteroids and supportive therapy for PNP, followed by complete surgical excision of the mediastinal mass once symptoms were controlled.OutcomesPostoperatively, corticosteroid therapy was continued, resulting in near-complete resolution of oral lesions. During a 20-month follow-up period, the patient remained free of MG recurrence and showed no new PNP lesions.LessonsThis case highlights a rare and diagnostically challenging overlap of CD, MG, and PNP. Accurate recognition required integration of histopathology, immunofluorescence, and serological testing, achieved through multidisciplinary collaboration across thoracic surgery, neurology, dermatology, and pathology. Clinicians should remain vigilant for such complex presentations, as early diagnosis and coordinated management are essential to improving outcomes in rare autoimmune-associated CD.